Hypoxanthine as a predictor of performance in highly trained athletes - Zielinski, J.; Krasinska, B.; Kusy, K. (International Journal of Sports Medicine, 2013)
Purine metabolism reflects the exercise-induced muscle adaptations and training status. This study evaluated the utility of plasma hypoxanthine in the prediction of actual sport performance. We studied male athletes: 28 triathletes (21.4±2.9 years), 12 long-distance runners (23.2±1.9 years), 13 middle-distance runners (22.9±1.8 years) and 18 sprinters (22.0±2.7 years). Season-best race times were considered, achieved over standard triathlon, 5 000 m, 1 500 m and 100 m, respectively. Incremental treadmill test was administered to determine maximum and "threshold" oxygen uptake. Resting and post-exercise plasma concentrations of hypoxanthine, xanthine, uric acid and lactate were measured as well as resting erythrocyte hypoxanthine-guanine phosphoribosyltransferase activity. Simple and multiple regression analyses were used to identify significant contributors to the variance in performance. Hypoxanthine considered alone explained more variance in triathletes, long-distance runners, middle-distance runners and sprinters (r 2=0.81, 0.81, 0.88 and 0.78, respectively) than models based on aerobic capacity and lactate (R 2=0.51, 0.37, 0.59 and 0.31, respectively). Combining purine metabolites and cardiorespiratory variables resulted in the best prediction (R 2=0.86, 0.93, 0.93 and 0.91; r=0.93, 0.96, 0.96 and 0.95, respectively). In summary, hypoxanthine is a strong predictor of performance in highly trained athletes and its prediction ability is very high regardless of sport specialization, spanning the continuum from speed-power to endurance disciplines.